2004
DOI: 10.1364/opex.12.006178
|View full text |Cite
|
Sign up to set email alerts
|

Rapid, depth-resolved light scattering measurements using Fourier domain, angle-resolved low coherence interferometry

Abstract: We present a novel angle-resolved low coherence interferometry scheme for rapid measurement of depth-resolved angular scattering distributions to enable determination of scatterer size via elastic scattering properties. Depth resolution is achieved using a superluminescent diode in a modified Mach-Zehnder interferometer with the mixed signal and reference fields dispersed by an imaging spectrograph. The spectrograph slit is located in a Fourier transform plane of the scattering sample, enabling angle-resolved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…Light scattering spectroscopy has been used in OCT to study the three-dimensional morphology of the cell nuclei [17,18]. Spectral characteristics of the objects were derived from OCT [19], and the authors of [20] studied molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Light scattering spectroscopy has been used in OCT to study the three-dimensional morphology of the cell nuclei [17,18]. Spectral characteristics of the objects were derived from OCT [19], and the authors of [20] studied molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Fourier domain a/LCI also realizes a significant increase in acquisition speed by collecting data across the entire angular range simultaneously by resolving each scattering angle using the multiple channels of an imaging spectrometer [26]. The combination of parallel collection in the depth and angular domains results in a 10 4 improvement in acquisition time, enabling interrogation of a single point in a sample in as little as 40 milliseconds.…”
Section: Fourier-domain A/lcimentioning
confidence: 99%
“…The angular distributions are compared to a theoretical basis, such as Mie theory in order to assess the most likely scattering geometry [26,29]. It has been shown that the angular distribution of the scattered intensity is related to the two-point spatial correlation function of the optical field through a Fourier transform [14] E( θ)…”
Section: Signal Analysismentioning
confidence: 99%
“…10 In order to enable clinical measurements, an a/LCI system based on an 18,000 element coherent (imaging) fiber bundle (Schott NA; Elmsford, NY) was developed that collected light in the spectral domain. 12 This system is able to collect and resolve light scattered from all depths in parallel in a single acquisition, decreasing the acquisition time by 3 orders of magnitude. Fourier-domain a/LCI was initially used to detect dysplasia in situ in human esophagus tissue clinically resected during esophago-gastrectomies.…”
Section: Introductionmentioning
confidence: 99%